Celiac disease - Mullin, Gerard E.; Rampertab, S. Devi (Clinical Gastroenterology, 2014)
Celiac Disease is an authoritative text intended to educate healthcare practitioners, gastroenterologists, physicians and nutritionists about the diverse manifestations, complications and management of gluten-sensitive enteropathy. The seventeen-chapter text provides the latest research on pathophysiology, including animal models, immunopathogenesis, genetics and the intestinal microflora. The book also features chapters on diagnosis, monitoring, complications and nutritional management, including therapies on the horizon. The text concludes with appendices that provide educational tools for symptom monitoring and dietary guidance. Written by specialists in their respective fields, Celiac Disease is a comprehensive resource that provides the healthcare practitioner an evidence-based practical guide to pathogenesis and therapy of celiac disease.